“It Cannot Be Emphasized Enough How Everything Is Interconnected”: Ecological Wisdom, Cross-Cultural Insight, and Pope Francis’ Social Teaching - Hrynkow, Christopher (The Trumpeter)

(untitled) (Athabasca University Press, 2018)
When understood as anthropogenic phenomena, contemporary social and ecological crises can be framed as moral issues, arising from human action and neglect of duties to marginalized human and ecological neighbours. In so much as the roots of these problematic outcomes lie in worldview, ecological wisdom can help in fostering spaces for integrated ethical responses to associated challenges like global climate change, social injustice, and ecological delegation. The present article highlights select instances of thinkers who express convergences between social and ecological concern by exploring cross-cultural perspectives on ecological wisdom. Then, with the aid of a green theo-ecoethical viewpoint informed by those perspectives, it maps relevant teachings of Pope Francis that are expressed in two of his most important exercises of his magisterial office: Evangelii Gaudium and Laudato Si’. As brought into view through dialogue with contemporary articulations of ecological wisdom, inclusive of overlapping Indigenous and academic insights, this approach helps discern a noteworthy measure of rhetorical support for socio-ecological flourishing found in the teaching of Pope Francis.